2017
DOI: 10.1016/j.juro.2016.10.104
|View full text |Cite
|
Sign up to set email alerts
|

First Clinical Experience with Extracorporeally Induced Destruction of Kidney Stones by Shock Waves

Abstract: We performed extracorporeally induced destruction of kidney stones on 72 patients. No complications have resulted from the tissue exposure to high energy shock waves. Clearance studies before and after the shock wave treatment indicate no changes in renal function. The method was used successfully in all patients with stones in the renal pelvis. In none of these patients was an open operation required. Two patients with ureteral stones also were treated with shock waves but had to be operated upon because of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…A meta-analysis has shown that a shock wave rate of 60 shocks per minute yields more favorable outcomes compared to a rate of 120 shocks per minute. 22 It is important to apply effective pressure from shock waves specifically to the stones, minimizing the impact on surrounding tissues. 23 Lowering the initial energy and shock wave frequency results in a reduced total number of shock waves and energy delivered, thereby decreasing the potential damage to the kidney, minimizing side effects, and improving patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis has shown that a shock wave rate of 60 shocks per minute yields more favorable outcomes compared to a rate of 120 shocks per minute. 22 It is important to apply effective pressure from shock waves specifically to the stones, minimizing the impact on surrounding tissues. 23 Lowering the initial energy and shock wave frequency results in a reduced total number of shock waves and energy delivered, thereby decreasing the potential damage to the kidney, minimizing side effects, and improving patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Інкрустацією та міграцією стента; 8. Виникненням болю в боці через рефлюкс сечі вгору по стенту [11,12,13,14,15].…”
Section: клінічна та експериментальна медицина / Clinical and Experim...unclassified
“…F OCUSED ultrasound surgery (FUS) has been routinely used to treat kidney stones since the 1980s [1]. In recent years, due to the noninvasive nature of this technique and the advancement of medical imaging [2], [3], FUS has quickly expanded its role to treat a variety of conditions, such as uterine fibroids, essential tremor [4], [5], bone metastases [6], and breast cancer [7], and enable drug delivery through major biological barriers [8]- [10].…”
Section: Introductionmentioning
confidence: 99%